2019
DOI: 10.3390/pathogens8030123
|View full text |Cite
|
Sign up to set email alerts
|

Cellular MicroRNA Expression Profile of Chicken Macrophages Infected with Newcastle Disease Virus Vaccine Strain LaSota

Abstract: Vaccines with live, low-virulence Newcastle disease virus (NDV) strains are still the most accepted prevention and control strategies for combating Newcastle disease (ND), a major viral disease that hampers the development of the poultry industry worldwide. However, the mechanism underlying vaccine-mediated innate cell immune responses remains unclear. Here, a high-throughput Illumina sequencing approach was employed to determine cellular miRNA expression profiles in chicken macrophages infected with the LaSot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These miRNAs may reciprocally regulate virus replication. Prior studies have shown that NDV regulates miRNA expression in the cells of avian origins (34)(35)(36)(37). NDV is an oncolytic virus and has widespread anti-tumor activities in preclinical animal models and in clinical trials (30).…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs may reciprocally regulate virus replication. Prior studies have shown that NDV regulates miRNA expression in the cells of avian origins (34)(35)(36)(37). NDV is an oncolytic virus and has widespread anti-tumor activities in preclinical animal models and in clinical trials (30).…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune cells such as macrophages and dendritic cells are activated in response to virus infection, which depending on the detection of pathogen-associated molecular patterns (PAMPs) by germline-encoded pattern-recognition receptors (PRRs), including Toll-like receptors (TLRs), Retinoic acid-inducible gene I (RIG-I)-like receptors (RLRS), Nod-like receptors and DNA sensors such as cGAS, IFI16, and DDX41 ( Oth et al, 2016 ; Eppensteiner et al, 2019 ). TLR3, 7, 8, and RLR members RIG-I and MDA5 detect the nucleic acid from RNA virus, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A (H1N1), vesicular stomatitis virus (VSV) ( El Chamy et al, 2008 ; Mu et al, 2019 ; Rehwinkel and Gack, 2020 ). TLR9 and DNA sensors recognize the viral DNA, after infection with DNA virus, such as herpes simplex virus-1 (HSV-1) and hepatitis B virus (HBV) ( Unterholzner et al, 2010 ; Gao et al, 2013 ; Xie et al, 2018 ; Briard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in humans have also demonstrated that cellular miRNAs are capable of regulating translation and replication in RNA viruses by directly binding to the virus genome [ 22 , 23 , 24 , 25 , 26 , 27 ]. In addition, studies in chickens have identified several miRNAs that are involved in immune responses against avian pathogens, such as avian pathogenic Escherichia coli (APEC), Newcastle disease virus (NDV), and Marek’s disease virus (MDV) [ 28 , 29 , 30 , 31 ]. Moreover, previous studies demonstrated the expression of miRNAs following AIV infections in chickens [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%